Nurses\' Perspectives on Human Dignity of Hospitalized Patients - Z Raee; H Abedi (Iran University of Medical Sciences, 2017)
Abstract Background & Aims: Respect for the human dignity as a moral principle is the professional responsibility of each nurse. Studies indicate the fact that the dignity of patients in care is neglected by healthcare professionals. This study aimed to determine the status of dignity in the hospitalized patients from the perspective of nurses in Iran. Material & Methods: In this cross-sectional study which conducted from 2012- 2013 in Isfahan's hospitals, 368 nurses were selected by cluster sampling method. Data were gathered through a questionnaire with Likert scale in the dimensions of "respecting privacy", "promotiong autonomy" and "nurse- patients respectful interaction" and were analyzed using descriptive and analytical statistics with SPSS software version 16. Results: Based on the findings from this study nurses were more satisfied with the patient's autonomy and the respectful communication and these componnets had the most mean (0.53 ± 2.43, 0.35 ± 2.40) and score (82%, 79%) respectively. Privacy of the patients had the lowest mean and scores (0.52 ± 2.43, 76%). Conclusion: This study showed the importance of being polite and respectful. A respectful tone of voice, using simple and understandable language, respond to every patient's question  and pay attention to gender of the nurse when the patient prefers a nurse of the same gender is so important in good communication between nurses and patients and require special attention.